1996
DOI: 10.4049/jimmunol.156.8.2700
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of CD80 and CD86 with CD28 and CTLA4.

Abstract: CD80 and CD86 are cell surface glycoproteins expressed on a variety of professional APCs. They have attracted much attention due to their function as potent costimulators of T lymphocyte function through their interaction with CD28 and possibly CTLA4. Because inhibitors of this interaction may have therapeutic relevance in human autoimmune disease, we investigated the properties of linear peptides derived from conserved regions of CTLA4 and CD80 known to be essential for binding. None of these peptides were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The importance o f the polyproline m otif in the CDR-3 like region of CD 28 for binding B7 ligands is well documented by mutagenesis (167,169). However, the results o f a previous study and our observations have shown that a synthetic peptide consisting o f the "M YPPPY' m otif alone does not constitute a minimal ligand binding epitope (178). In general, a "functional epitope" defined by mutagenesis is much smaller that the "structural epitope" seen in the three-dimensional structures.…”
Section: The Importance Of the Poplyproline M Otif And The Pp Ii Heli...contrasting
confidence: 50%
“…The importance o f the polyproline m otif in the CDR-3 like region of CD 28 for binding B7 ligands is well documented by mutagenesis (167,169). However, the results o f a previous study and our observations have shown that a synthetic peptide consisting o f the "M YPPPY' m otif alone does not constitute a minimal ligand binding epitope (178). In general, a "functional epitope" defined by mutagenesis is much smaller that the "structural epitope" seen in the three-dimensional structures.…”
Section: The Importance Of the Poplyproline M Otif And The Pp Ii Heli...contrasting
confidence: 50%
“…CD28 signaling is triggered by its counter receptors CD80/CD86 [expressed on antigen-presenting cells (APC)] and is regulated by a physiological antagonist (cytotoxic T lymphocyte antigen-4, CD152; CTLA4) expressed by T cells. CTLA4 binds to CD80/86 with high avidity and prevents T cell activation by blocking intracellular CD28 downstream events 4 . The inhibition of CD28-driven costimulation can be the ideal target to downregulate T cell activity in Th1-mediated diseases such as rheumatoid arthritis (RA) and psoriatic arthritis (PsA).…”
mentioning
confidence: 99%